The Role of Siyāsah Shar'iyyah in Analyzing and Addressing Land Disputes - Syafa'at Anugrah Pradana; Hasim, Hasanuddin; Haq, Muhammad Imam Dhiyaul (Mazahibuna: Jurnal Perbandingan Mazhab, 2024)
Disputes are often reported from complexities related to land ownership, particularly when multiple parties lay claim to a specific plot acquired through gifting or inheritance. Public objections predominantly center around preventing inaccuracies in the transfer of ownership rights during the recording of land blocks at National Land Office (BPN) concerning blocking of ownership rights. Therefore, this study aims to examine the prevalent issues encountered during the recording of land title certificate, with a specific focus on the common land disputes that lead to legal proceedings. An analytical framework of siyāsah shar'iyyah is adopted with empirical juridical methodology using a socio-juridical perspective. The data-gathering method comprises three distinct stages, namely reduction, presentation, and conclusion. The results show that the submission of a plot of land for registration cannot be executed by any arbitrary party. A clear understanding of applicant's status and the rationale behind the request is necessary to restrict the use of land effectively. In this context, the registration of land blocks has diverse effects in terms of economic, socio-cultural, and legal assurance. The challenges encountered in the act of obstructing are predominantly rooted in the administrative procedure. Therefore, the proposed remedy includes the use of technology based on electronic systems to effectively disseminate information to the public. In this jurisdiction, land ownership is primarily governed by Sharia law, which views documenting property rights as a method of promoting good governance. Meanwhile, zoning arrangements serve as an alternative for documenting land blocking, mitigating potential ownership issues in the future.